2016
DOI: 10.1891/1945-8959.15.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Creativity in the Educational Design Context: An Exploration of the Effects of Design Project-Oriented Methods on Students’ Evocation Processes and Creative Output

Abstract: One of the challenges in today’s society is to satisfy the growing need for creativity and innovation, especially in design contexts, where designers have to come up with products that are both new and adapted to their users. Although designers’ professional experience is crucial, we consider that their creative skills can be nurtured in design schools. We therefore explored the effects of two types of design project-oriented methods, which were operationalized as specific courses offered to design students. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…For example, although it has been postulated that prior creative abilities moderate the effectiveness of an enhancement method (e.g., Agnoli et al, 2018), prior creative ability was rarely assessed in the primary studies. Only two studies explicitly used a gifted study sample from arts education (Bonnardel & Didier, 2016; Ulger, 2016). Both studies showed mean effect sizes substantially above our meta-analytical estimate, suggesting an improved ability to enhance creative performance in gifted participants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although it has been postulated that prior creative abilities moderate the effectiveness of an enhancement method (e.g., Agnoli et al, 2018), prior creative ability was rarely assessed in the primary studies. Only two studies explicitly used a gifted study sample from arts education (Bonnardel & Didier, 2016; Ulger, 2016). Both studies showed mean effect sizes substantially above our meta-analytical estimate, suggesting an improved ability to enhance creative performance in gifted participants.…”
Section: Discussionmentioning
confidence: 99%
“…For Bonnardel and Didier ( 2016 ), in design, it is important to abandon the everyday to explore the world of ideas and to propose innovative solutions. However, in the present study, pupils had rarely declared they abandoned an idea.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, the activity of design demands identifying and analyzing the problem and finding innovative and appropriate situations for realization ( Bonnardel and Didier 2016 ). The activity of design includes different stages of the creative process such as definition, reflection, structuration of ideas, dealing with constraints, documenting, and taking decisions ( Bonnardel 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no doubt that certain students' professional quality and skills will increase after they have received professional training and the clothes design does not require the memorisation of knowledge points but engage with innovative thinking (Lulu, 2020). Creativity usually defines as is usually understood, is to be capable of making something that is both original and suitable, and such expectations for designers' actions are consistent with such conceptions of creativity (Bonnardel & Didier, 2016).…”
Section: Understanding Creativity For Fashion Studentsmentioning
confidence: 94%